A facile method to prepare ultra-wideband anti-reflective borosilicate glass with subwavelength structure surface. Issue 11 (1st August 2019) - Yu, Hang; Xiao, Xiudi; Kang, Shiliang; Chen, Qinpeng; Dong, Guoping
Abstract: Anti-reflective (AR) films have been widely investigated due to their various applications in optoelectronic devices. Among all the investigation, the manufacturing method is the most popular research field which directly determines the performance of anti-reflective films. Herein, Na2 HPO4 and AlCl3 mixed neutral solution were used to etch the surface of K9 glass matrix to obtain the AR structure. The morphology of SEM images indicated that subwavelength structure (SWS) was formed on the glass surface via precisely controlling the solution concentration, treatment time and temperature. Owing to the porous structure, the refractive index mutation of the interface between air and glassss can be effectively weakened. Therefore, the integral transmittance, covering the whole visible light (VIS) to near-infrared (NIR) wavelength (300–2500 nm), of glass matrix was increased remarkably to 95.77%, much higher than 87.72% of blank glass, achieving the effect of ultra-wideband anti-reflection. Particularly, the transmittance at 520 nm and 1990 nm can even reach to 99.14% and 97.86%, respectively. According to the composite analysis and reaction process, Al 3+ ions act as both the regulator of the solution pH and part of the new-formed glass skeleton, resulting in the more uniform and regular SWS on the glass surface. Moreover, in virtue of -OH in silanol (Si-OH) on the expanded glass surface attracting more H2 O molecules or additional silylation modification on glass surface repulsing H2 O molecules, the surface characteristics of AR glass with SWS films can be easily turned between hydrophilic and hydrophobic in order to meet the requirements of various application environments. These ultra-wideband AR glasses with controllable hydrophilic and hydrophobic properties are expected to be applied in many optoelectronic fields.